Diseño de un recorrido virtual de la Universidad Técnica de Cotopaxi (matriz), para orientar a los estudiantes y visitantes - Oyos Caiza, Evelyn Fernanda (2017)
This research project aims to reach in all those who are part of the Technical University of Cotopaxi, acquiring knowledge about the institution's dependencies location by an interactive virtual tour, so the photographic technique 360 ° is used, which is part of the technological trends currently, contributing to the institution placement improvement. This virtual route strategy indirectly generates a marketing bonus for the institution, since the technique of 360 ° photography is being widely used by large companies at national and international level, to guide, show and sell their architectural projects, as well as in the educational, cultural and technological fields. The structural organization chart proposed by the institution and in turn the plans were taken to uncover and analyze the route that the user makes within the institution, for which two surfing maps were made too. For the virtual research tour the Christopher Jones´ Transparent Box methodologys was implemented.